2020
DOI: 10.1038/s41467-020-19936-x
|View full text |Cite
|
Sign up to set email alerts
|

Distributed control of motor circuits for backward walking in Drosophila

Abstract: How do descending inputs from the brain control leg motor circuits to change how an animal walks? Conceptually, descending neurons are thought to function either as command-type neurons, in which a single type of descending neuron exerts a high-level control to elicit a coordinated change in motor output, or through a population coding mechanism, whereby a group of neurons, each with local effects, act in combination to elicit a global motor response. The Drosophila Moonwalker Descending Neurons (MDNs), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 64 publications
4
44
1
Order By: Relevance
“…Elegant recent work has shown that initiation of forward walking requires the forelegs, innervated by motor neurons in the prothoracic segment, whereas initiation of backward walking requires the hindlegs, innervated by motor neuron in the metathoracic segment (Feng et al, 2020). This is consistent with our finding that the adult Pair1 neuron innervates the prothoracic neuropil, a site well-positioned to arrest motor activity driving foreleg stepping and initiation of forward locomotion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Elegant recent work has shown that initiation of forward walking requires the forelegs, innervated by motor neurons in the prothoracic segment, whereas initiation of backward walking requires the hindlegs, innervated by motor neuron in the metathoracic segment (Feng et al, 2020). This is consistent with our finding that the adult Pair1 neuron innervates the prothoracic neuropil, a site well-positioned to arrest motor activity driving foreleg stepping and initiation of forward locomotion.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our finding that the adult Pair1 neuron innervates the prothoracic neuropil, a site well-positioned to arrest motor activity driving foreleg stepping and initiation of forward locomotion. Similarly, adult MDN synaptic partners primarily innervate the metathoracic neuromere (Feng et al, 2020), a good location for inducing hindleg stepping and initiation of backward walking. A similar spatial segregation is likely to occur in the larva, where forward crawling is induced by A27h in posterior segments, and backward crawling is induced in anterior segments (Fushiki et al, 2016;Tastekin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the DN neurons in question innervate a variety of leg and wing neuropils in the VNC (Namiki et al, 2018), suggesting that control of different actuators is somewhat integrated or coordinated in the LAL. PFL2 and PFL3 neurons also reach the moonwalker neuron MDN (Bidaye et al, 2014;Feng et al, 2020), which has a bilateral innervation pattern and is known to drive backward walking. This connection is almost exclusively contralateral (Figure 63-figure supplement 1A,B), a suggestion that the MDN could also be involved in asymmetric behaviors.…”
Section: Interactions With Visual Projection Pathwaysmentioning
confidence: 99%
“…How much of the adult MDN-Pair1 circuit is present in the larvae? Recent work mapping the adult MDN circuit has identified over 30 VNC neurons downstream of MDN, including the LBL40 and LUL130 neurons required for hindleg backward stepping (Figure 5; Feng et al, 2020). Recent work has also identified adult neurons important for forward walking (Bidaye et al, 2020), but their relationship to adult MDN is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant recent work has shown that initiation of forward walking requires the forelegs, innervated by motor neurons in the prothoracic segment, whereas initiation of backward walking requires the hindlegs, innervated by motor neuron in the metathoracic segment (Feng et al, 2020). Similarly, adult MDN synaptic partners primarily innervate the metathoracic (T3) neuromere (Feng et al, 2020), a good location for inducing hindleg stepping and initiation of backward walking. A similar spatial segregation is likely to occur in the larva, where forward crawling is induced by A27h in posterior segments, and backward crawling is induced in anterior segments (Fushiki et al, 2016;Tastekin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%